Incorporation of eggshell ash in the stabilization of clayey subgrade in Apurimac, Peru (Gaceta Técnica, 2025)
The stabilization of clayey soils is a persistent challenge in civil engineering, particularly in regions with infrastructure projects in expansive soil areas. This study evaluates the effectiveness of incorporating eggshell ash (CCH) to improve the mechanical properties of clayey subgrades on Av. Alisos, Anccohayllo, Apurímac, Peru. The research included field sampling and laboratory tests to analyze the California Bearing Ratio (CBR), compaction characteristics, and plasticity of soil samples with varying CCH percentages of 10%, 15%, and 20%. Results showed significant improvement in CBR values, with a 71,79% increase using 20% CCH, indicating a substantial increase in soil bearing capacity. Additionally, the Maximum Dry Density (MDD) increased and the Optimum Moisture Content (OMC) decreased, suggesting better soil compaction and stability. Although the effect on plasticity was not statistically significant, a slight reduction was observed. This study concludes that CCH is a viable and sustainable additive for stabilizing clayey subgrades, offering an environmentally friendly alternative through the reuse of agricultural waste